Analysis of the Ability of High School Students in Solving Science Literacy Questions Based on the Rasch Model - Saiyidah Mahtari; Misbah Misbah; Suryati Suryati (Kasuari: Physics Education Journal (KPEJ), 2019)
This study aims to describe aspects of students 'abilities in solving problems of students' scientific literacy problems based on the RASCH model. This research uses descriptive quantitative research design with survey research methods. The research subjects were 33 students of class XII IPA 2 of SMAN 6 Banjarmasin. Data collection techniques were carried out by using a scientific literacy test consisting of 9 items about the description of dynamic electrical matter. The results of the research data were analyzed using the RASCH model using the Winstep program to obtain logit values. The results showed that the average student logit value was 1.75 logit, this value was less than 0.0 logit. This indicates that students' ability to solve scientific literacy questions is still low, so students need to be trained in scientific literacy through classroom learning.